Climate Smart Agriculture in the Eastern Caribbean States: Implementing an integrated approach to reduce the effects of drought on farming in the New River area: New River Farmers’ Cooperative Society, New River Estate, St. James, Nev - IICA, Basseterre (Saint Kitts and Nevis) (2021)
Climate Smart Agriculture (CSA) is an approach to developing the technical, policy and investment conditions to achieve sustainable agricultural development for food security under climate change. The goal of CSA is to enable the sector to transition towards more climate-resilient production systems and more sustainable livelihoods in the presence of climate change stressors and climate variability.